Fibrodysplasia ossificans progressiva without characteristic skeletal anomalies - Ulusoy, Hasan (Springer Heidelberg, 2012)
Fibrodysplasia ossificans progressiva (FOP) is a rare but extremely disabling genetic disease of the skeletal system. This disease is characterized by progression of heterotopic ossification within skeletal muscles, ligaments and tendons. Most patients with FOP are misdiagnosed early in life before the appearance of heterotopic ossification and undergo diagnostic procedures such as biopsy that can cause lifelong disability. Almost all of the patients have some peculiar congenital anomalies, including short great toes, hallux valgus, short thumbs and hypoplasia of digital phalanges. These congenital defects support the diagnosis of FOP, but are not constantly observed in the totality of patients. If necessary, genetic studies can be performed to confirm the diagnosis. Once diagnosed, patients should be advised in order to avoid unnecessary traumas, surgical procedures, biopsies, intramuscular injections and vaccinations. Here, we describe a patient with FOP without characteristic congenital skeletal anomalies.
Keywords: Fibrodysplasia ossificans progressiva; Myositis ossificans progressiva; Heterotopic ossification